Serial changes of computed tomographic peritoneogram in patients with symptomatic ultrafiltration failure complicating continuous ambulatory peritoneal dialysis. Issue 3 (21st December 2016) - Cheung, Michelle; Chu, Ferdinand SK; Kwan, Lorraine PY
Abstract: Introduction: It is well‐known that continuous ambulatory peritoneal dialysis (CAPD) is associated with complications. And some of these complications are well‐demonstrated as abnormalities on computed tomographic peritoneogram (CTP). The objective of our study is to document the serial changes of these complications. Methods: We retrospectively reviewed 125 patients treated with CAPD for end staged renal failure (ESRF) who had CTP conducted in our hospital between December 2006 and August 2015. A total of 164 ( n = 164) CTPs were performed. Patients with only one CTP performed were excluded from our study. A retrospective review of 68 serial CTPs studies on 28 patients during the 9‐year period was undertaken. We looked into the serial changes on CTP. Results: Among the 28 patients who had serial imaging, 46.43% of patients were found to have retroperitoneal leakage; 92.31% of them showed resolution in subsequent serial CTP. 21.43% of patients had anterior abdominal wall leakage; none of them resolved in subsequent CTP. 14.29% of patients were found to have inguinal hernias; 75% of them showed interval progression in subsequent serial CTPs. Conclusion: Retroperitoneal leakage is a common complication in patients on CAPD and tends to resolve whereas other complications including anterior abdominal wall leakage and hernias are unlikely to resolve and may progress further.